Does the Catford drum give an accurate assessment of acuity?. Issue 9 (September 1981) - Atkinson, J; Braddick, O; Pimm-Smith, E; Ayling, L; Sawyer, R
Abstract : Adult emmetropes and myopes were tested with the Catford drum and the results compared with subjective (Landolt C) acuity. For he emmetropes the Catford drum was found to overestimate visual acuity by a factor of approximately 4. For myopes, and emmetropes viewing through plus lenses, the discrepancies were much larger. Since the Catford drum not only overestimates acuity but will do so by a factor which varies for different visual disorders, caution is needed in clinical interpretation of results obtained with it.